Boredom and Media Multitasking - Drody, Allison C.; Ralph, Brandon C. W.; Danckert, James; Smilek, Daniel (Frontiers in Psychology, 2022)
Media multitasking entails simultaneously engaging in multiple tasks when at least one of the tasks involves media (e.g., online activities, streaming videos, etc.). Across two studies, we investigated one potential trigger of media multitasking, state boredom, and its relation to media multitasking. To this end, we manipulated participants’ levels of state boredom using video mood inductions prior to administering an attention-demanding 2-back task during which participants could media multitask by playing a task-irrelevant video. We also examined whether trait boredom proneness was associated media multitasking. We found no direct evidence that state boredom leads to media multitasking. However, trait boredom proneness correlated with greater amounts of media multitasking in Experiment 1, but not in Experiment 2. Surprisingly, in both experiments, post-task ratings of state boredom were equivalent across conditions, alerting us to the short-lived effects of video mood inductions and the boring nature of cognitive tasks.